Seventy times seven: a true story of murder and mercy - Mar, Alex (Penguin Press, 2023)
"A thought-provoking, masterfully told work of literary journalism about a shocking crime committed by a teenager-and its even more shocking aftermath In 1985 in Gary, Indiana, a black teenaged girl kills an elderly white woman in a robbery gone wrong. The shock and awe of the case captivates the state, whose citizens cry out for vengeance. Soon after, Paula Cooper, the fifteen-year-old killer, is sentenced to death. Indiana's minimum age for the death penalty is, at that time, ten years old. In Seventy Times Seven, Alex Mar tells the unforgettable story of this single act of violence and its stunning aftermath. The image of a teenaged girl on death row will reverberate miles from Gary and link a varied cast of characters: a female public defender from the northeast, two enterprising Italian journalists, a Franciscan friar with the ear of the Pope, and, in an unlikely twist, the grandson of the victim, who dedicates himself to saving Paula's life. As a girl waits on death row, her fate sparks a debate that not only animates legal circles but also raises universal questions about the value of human life: What is the purpose of criminal justice, especially its harshest penalties? Is forgiveness an act of desperation or of profound bravery? What extreme degrees of empathy might humans be capable of, if given the chance? Seventy Times Seven opens with a murder and a death sentence, but it is above all about the will to live-to survive, to grow, to change-against the steepest odds. Tirelessly researched and told with intimacy and precision, it brings a haunting chapter in the history of our criminal justice system to astonishing life"--